Functional Composites, Ceramics and Glasses Special topic volume with invited peer-reviewed papers only - Rajagukguk, Juniastel; Nugroho, Agustinus Agung; Xin, Shixuan; Antoniac, Iulian; Requena, Guillermo (Materials Science Forum, 2023)
This special edition is dedicated to analysing properties and possible methods of treatment and applications of the comprehensive nomenclature of modern special and functional materials: polymers and composites, ceramics, metal oxides, dielectrics, semiconductors, glasses, etc. This edition will be helpful to researchers and engineers whose professional activity is related to materials science, micro- and optoelectronics, optical engineering and machinery. Polymer, Composite, Ceramics, Photocatalytic Activity, Mechanical Properties, Electrochemical Properties, Crystal Structure, Magnetic Properties, Nanoparticles, Photoluminescence Properties, Dielectric Properties Materials Science, Nanoscience.